Implementation of Discovery Learning Model Assisted by Mathigon on Mathematics Learning Outcomes - Luqyana Jasmine Lathifah; Edwin Musdi; Mirna Mirna; Suherman Suherman (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
This research was motivated by the low mathematics learning outcomes resulting from students' low activeness and the not yet optimal use of technology-based learning media. One alternative that can be applied is the Mathigon-assisted Discovery Learning model. This study aims to determine whether the mathematics learning outcomes of students taught using the Mathigon-assisted Discovery Learning model are better than those of students taught using conventional learning. This study used a quasi-experimental method with a Non-equivalent Posttest-Only Control Group Design. The population of this study was all eighth-grade students of SMP Negeri 1 Hiliran Gumanti in the 2025/2026 Academic Year. The sample was selected using a cluster random sampling technique, namely class VIII.2 (26 students) as the experimental class and class VIII.3 (25 students) as the control class. The equivalence of the initial abilities of the two classes was based on the Odd Semester Examination scores in mathematics. The experimental class received instruction using the Mathigon-assisted Discovery Learning model, while the control class received conventional instruction. The research instrument was an essay test that had met the criteria of validity and reliability. The data were analyzed using descriptive statistics, normality tests, homogeneity tests, and t-tests with the assistance of Minitab 18. The results showed that the mathematics learning outcomes of students taught using the Mathigon-assisted Discovery Learning model were better than those of students taught using conventional learning, with a mean score of 79.74 for the experimental class and a p-value = 0.004 < 0.05. The effect size analysis using Cohen's d of 0.79 indicated a medium effect, which suggests that the implementation of this model made a fairly significant contribution to the mathematics learning outcomes of eighth-grade students at SMP Negeri 1 Hiliran Gumanti.